Renal Cell Carcinoma with Synchronous Metastasis to the Calcaneus and Metachronous Metastases to the Ovary and Gallbladder - Jasper Decoene; Filip Ameye; Evelyne Lerut; Raymond Oyen; Hein Van Poppel; Steven Joniau (Case Reports in Medicine)
Renal cell carcinomas (RCCs) are known for their unpredictable metastatic pattern. We present the case of a 63-year-old woman who initially presented in 1992 with a metastasis in the left calcaneus that led to the discovery of RCC. In 1998, a new metastasis was found in the ovary. In 2008, the diagnosis of a gallbladder metastasis was made. All metastases were surgically removed; no additional systemic therapies were used. Aggressive surgical treatment can prolong the survival of patients with resectable metastases. Patterns of metastasis are discussed, and a brief review of the literature is given regarding each localization.